Sexual violence against girls and adolescents: socio-cultural principle - Lucich Rivera, Esther Amelia (2011)
The objective is to contribute to explain the social problem of sexual violence against girls and adolescents. The interviewed group were girls from 6 to 15 years old who were sexually abused by their fathers; additionally, we were able to interview 9 mothers of these girls were interviewed. The interviews were semi-structured and in depth in order to make a posterior content analysis. Results were built by the gender approach and we call them «socio-cultural principle» which consists of patriarchy and power and sexual division of housework. It is described how parents see their daughters as the object of arguing or admiration and the existence of differences in patterns of socialization between male and female children. Finally it is introduced the authoritarian conception of these minors, being considered as miniature adults without personal physical spaces. This research was conducted between 2004 and 2006.